ANALYSIS OF WATER DEMAND AND AVAILABILITY IN THE PRUMPUNG WATERSHED, TUBAN - Rony Zakariya; Andi Patriadi; Esti Wulandari (Acitya Wisesa: Journal of Multidisciplinary Research, 2026)
Water constitutes a vital natural resource supporting human life, agricultural activities, and regional development. Limited water availability coupled with continuously increasing water demand due to population growth and agricultural activities necessitates data-based water resource planning and management. This research aimed to analyze water demand and water availability in the Prumpung Watershed, Tuban Regency, for the 2025-2029 projection period. The research employed a descriptive quantitative approach utilizing population, land use, and rainfall data. Domestic water demand was calculated based on per capita consumption standards and population projections, while non-domestic water demand was calculated from rice field irrigation requirements based on land area and cropping intensity. Water availability was calculated based on surface runoff volume obtained from annual rainfall, runoff coefficient, and watershed area. The analysis results indicate that domestic water demand increases from 2,389,812 m³ in 2025 to 2,491,776 m³ in 2029. Non-domestic water demand increases from 91,034,789.98 m³ to 92,943,134.36 m³, bringing total water demand from 93,424,602.32 m³ to 95,434,910.78 m³. Meanwhile, average annual water availability amounts to 84,586,033.31 m³. The comparison between water demand and water availability demonstrates that water demand exceeds water availability throughout all projection years. Therefore, efforts to improve water use efficiency, particularly in the irrigation sector, and catchment area conservation are required to maintain water resource sustainability in the Prumpung Watershed.